Chromosomal Microstructure Diversity in Three Astyanax (Characiformes, Characidae) Species: Comparative Analysis of the Chromosomal Locations of the 18S and 5S rDNAs - Piscor, Diovani [UNESP]; Alves, Anderson Luis; Parise-Maltempi, Patricia Pasquali [UNESP] (Mary Ann Liebert, Inc, 2015)
The species of genus Astyanax is widely distributed in freshwater neotropical zones. Astyanax is considered to be taxonomically confused, similar to other genera placed incertae sedis in Characidae. The cytogenetics of this genus is well characterized; species vary widely in diploid number, from 2n=36 chromosomes in Astyanax schubarti to 2n=50 for most species studied. The size, number, and position of different cytological markers vary among species and populations of Astyanax. We analyzed the karyotypes of individuals from three Astyanax species (Astyanax abramis, Astyanax altiparanae, and Astyanax eigenmanniorum) from populations not previously analyzed. We describe variations in several cytogenetic markers and the karyotypic relationships between them, specifically focusing on the characteristics of the conserved and divergent locations of the ribosomal genes. Our data are useful for establishing relationships between species and for investigating the karyotype evolution within the genus.